Self-efficacy, social support, and their relationship to treatment adherence in pulmonary tuberculosis: A cross-sectional study - Heltty, Heltty; Masriwati, Siti; Yati, Mimi; Saltar, La Ode; Dina, Hasniah (Palembang MediRose Publisher, 2025)
Background: Tuberculosis (TB) remains a leading global health problem, with high morbidity and mortality. Adherence to long-term treatment regimens is essential to eradicate Mycobacterium tuberculosis and prevent drug resistance, yet many patients face psychosocial barriers that reduce adherence Objective: To examine the association of self-efficacy and social support with treatment adherence among patients with pulmonary TB. Methods: This cross-sectional study was conducted in the Outpatient Department of Kendari City Hospital, Indonesia, from April to June 2024. Using consecutive sampling, 88 patients with pulmonary TB aged 20 to 50 years who were undergoing treatment and met inclusion criteria were enrolled. Self-efficacy was assessed using the General Self-Efficacy Scale, social support with the Multidimensional Scale of Perceived Social Support, and treatment adherence with the 8-item Morisky Medication Adherence Scale. Associations were analyzed using chi-square tests and multiple linear regression. Results: Among 88 participants, 63.6% demonstrated high adherence, 63.6% reported good self-efficacy, and 63.6% reported high social support. Self-efficacy was positively associated with treatment adherence (r=0.265; p=0.024). Similarly, social support was positively associated with adherence (r=0.263; p=0.025). Regression analysis indicated that social support had the greatest influence on adherence (B=0.257; p=0.013), explaining 13.6% of the variance in adherence when combined with self-efficacy. Conclusion: Self-efficacy and social support are significant predictors of treatment adherence in pulmonary TB patients. Nursing interventions that enhance patient confidence and mobilize family and community support may improve adherence and optimize TB treatment outcomes